187 OS-ENRICHED DOMAIN IN AN ARCHEAN MANTLE PLUME: EVIDENCE FROM 2.8 GA KOMATIITES OF THE KOSTOMUKSHA GREENSTONE BELT, NW BALTIC SHIELD - Puchtel I.S.; Brügmann G.E.; Hofmann A.W. (My University, 2001)
The Re–Os data on Archean komatiites from the Kostomuksha greenstone belt in the Baltic Shield are presented. This greenstone belt has been previously interpreted to represent a former oceanic plateau formed by the emplacement of an ancient plume head [Puchtel et al., Earth Planet. Sci. Lett. 155 (1998) 57–74]. Samples of flowtop breccia, spinifex-textured and cumulate komatiites and a chromite separate, all collected from the core of a 300 m deep diamond drill hole, yielded a Re–Os isochron with an age of 2795±40 Ma and an initial 187Os/188Os of 0.1117±0.0011 (γ187Os=+3.6±1.0). The high positive γ187Os(T) implies that the komatiites were derived from a mantle source with a time-integrated suprachondritic Re/Os ratio. Recycling of oceanic lithosphere to produce the enriched 187Os isotope signature is considered unlikely, as 15–25% crustal component is required to be incorporated into the plume source as early as 3.5–4.3 Ga. Such a substantial proportion of mafic material in the source would likely destroy the major and trace element characteristics of the komatiites. Our tentative interpretation is that the 187Os-enrichment in the Kostomuksha plume represents an outer core signature. If confirmed by the ongoing Pt–Os isotope studies, the results would provide evidence for the existence of whole-mantle convection in the late Archean, and might place constraints on the timing of core differentiation in the early Earth.
Keywords: Archean; Kostomuksha; komatiites; Re–Os data; Baltic Shield; Precambrian::Archean; Докембрий::Архей